2000
DOI: 10.1007/s007050070027
|View full text |Cite
|
Sign up to set email alerts
|

EHV-1 glycoprotein D (EHV-1 gD) is required for virus entry and cell-cell fusion, and an EHV-1 gD deletion mutant induces a protective immune response in mice

Abstract: Insertional mutagenesis was used to construct an equine herpesvirus 1 (EHV-1) mutant in which the open reading frame for glycoprotein D was replaced by a lacZ cassette. This gD deletion mutant (delta gD EHV-1) was unable to infect normally permissive RK cells in culture, but could be propagated in an EHV-1 gD-expressing cell line (RK/gD). Phenotypically complemented delta gD EHV-1 was able to infect RK cells, but did not spread to form syncytial plaques as seen with wild type EHV-1 or with delta gD EHV-1 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…In this same study, EHV-1 was also shown to enter equine peripheral blood mononuclear cells (PBMCs) via endocytosis, suggesting that the endocytic mode of EHV-1 occurs in cells of equine origin. Regardless of the mode of entry or the cell type infected, EHV-1 entry in all cases requires gD (10,14,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this same study, EHV-1 was also shown to enter equine peripheral blood mononuclear cells (PBMCs) via endocytosis, suggesting that the endocytic mode of EHV-1 occurs in cells of equine origin. Regardless of the mode of entry or the cell type infected, EHV-1 entry in all cases requires gD (10,14,45).…”
Section: Discussionmentioning
confidence: 99%
“…While these electrostatic interactions mediate virus binding, they do not trigger the entry of the virus into cells. For entry to proceed, a secondary triggering event mediated by gD must occur (10,14). After entry is initiated, EHV-1 enters cells either by directly fusing with the plasma membrane or via endocytosis (17).…”
mentioning
confidence: 99%
“…PRV and BHV-1 together with EHV-1 and Varicella-zoster virus form the Varicellovirus genus within the Alphaherpesvirinae subfamily (30). Whereas the functions of several individual EHV-1 envelope proteins, such as glycoprotein B (gB), gC, gD, gE, and gM, have been analyzed in some detail (4,18,(20)(21)(22), studies on the functions of the putative gE/gI, gH/gL, or gM/UL49.5 complexes have not yet been performed.…”
mentioning
confidence: 99%
“…Using gD deletion mutants of these viruses, investigators previously established that viral particles lacking envelope gD fail to penetrate target cells while maintaining the ability to attach to the cell surface (10)(11)(12)(13)(14). Not all viruses in the subfamily Alphaherpesvirinae, however, have or express the gD gene.…”
Section: Discussionmentioning
confidence: 99%
“…A key role of gD homologs in cell entry was established for all known alphaherpesviruses expressing the protein, including herpes simplex virus 1 (HSV-1), pseudorabies virus (PRV), bovine herpesvirus 1 (BHV-1), and equine herpesvirus 1 (EHV-1). Investigations of deletion mutants of these viruses showed that gD is essential for virus penetration into target cells (10)(11)(12)(13)(14). Numerous studies showing complete inhibition of virus cell entry by monoclonal gD antibodies, soluble recombinant gD protein, or soluble gD receptors further confirmed the crucial role of gD in in vitro infectivity of alphaherpesviruses (15)(16)(17)(18).…”
mentioning
confidence: 99%